New strategy of personalized tissue regeneration: when autologous platelet concentrates encounter biomaterials - Ren, Sicong; Wang, Hanchi; Ma, Sijia; Zhou, Jing; Zhai, Jingjie; Zhu, Yuemeng; Chen, Sheng; Chen, Siyu; Jia, Kewen; Xu, Wenzhou; Zhou, Yanmin (Frontiers in Bioengineering and Biotechnology, 2023)
Components in blood play an important role in wound healing and subsequent tissue regeneration processes. The fibrin matrix and various bioactive molecules work together to participate in this complex yet vital biological process. As a means of personalized medicine, autologous platelet concentrates have become an integral part of various tissue regeneration strategies. Here, we focus on how autologous platelet concentrates play a role in each stage of tissue healing, as well as how they work in conjunction with different types of biomaterials to participate in this process. In particular, we highlight the use of various biomaterials to protect, deliver and enhance these libraries of biomolecules, thereby overcoming the inherent disadvantages of autologous platelet concentrates and enabling them to function better in tissue regeneration.